1996
DOI: 10.1111/j.1365-3059.1996.tb02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum gloeosporioides as the cause of stem tip dieback of cassava

Abstract: A fungus with morphological features corresponding to the group species Colletorichum gloeosporioides was consistently isolated from cassava with shoots showing dieback symptoms in Ghana. When four locally‐grown cultivars were inoculated with isolates of the fungus, they developed disease symptoms, which consisted of discrete dark brown lesions on the stems followed by defoliation. Koch's postulates were completed by re‐isolating the fungus from the inoculated plants. The relatedness of the isolates lo other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Comparing the aligned nucleotide sequences of the D2 region (180 nucleotides) of the studied isolates, along with data of other previously-identified Colletotrichum species from LARS collection Moses et al, 1996;Sherriff et al, 1994), the maximum number of differences among the aligned bases was 16, i.e. 8.9%.…”
Section: Molecular Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing the aligned nucleotide sequences of the D2 region (180 nucleotides) of the studied isolates, along with data of other previously-identified Colletotrichum species from LARS collection Moses et al, 1996;Sherriff et al, 1994), the maximum number of differences among the aligned bases was 16, i.e. 8.9%.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Isolates LARS 909 and 938 (G3) were identical to the ones obtained from Stylosanthes spp., and isolates from G4 (LARS 912,913,917,924,927,931,and 940) differed by two nucleotides from those in Stylosanthes spp., and by only one nucleotide from those on A. virginica, M. indica or C. melo. Different regions (D1, D2) of the LSU rDNA and intergenic sequences (ITS1, ITS2) have more variation in their rate of evolution than do the domains of the small subunit, being useful to distinguish groups in closely related taxa, like in the genus Colletotrichum Kohn, 1992;Moses et al, 1996;Moriwaki et al, 2002). Sherriff et al (1994; observed that sequence data from the D2 region was as informative as the combined D1, D2 and ITS2 regions (886 bp) in revealing the differences and relationships in Colletotrichum, since it has a sufficient proportion of sequence divergence to distinguish between the main species of this genus.…”
Section: Molecular Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Colletotrichum postharvest fruit rots are responsible for major economic losses, with severe infections resulting in up to 100 % loss during storage (Prusky 1996). Colletotrichum diseases also produce substantial damage on important subsistence crops including lentil, cowpea, yam, banana, sorghum, and cassava (Adegbite and Amusa 2008;Chona 1980;Chongo et al 2002;Finlay and Brown 1993;Green and Simons 1994;Moses et al 1996;Moura-Costa et al 1993).…”
Section: Introductionmentioning
confidence: 99%